Intact polar lipids and water column chemistry from the eastern tropical south Pacific in February of 2018 - Sebastian Cantarero; Carlos Henríquez-Castillo; Nadia Dildar; Cristian A Vargas; Peter von Dassow; Marcela Cornejo-D extquotesingleOttone; Julio Sepúlveda (PANGAEA, 2020)
These data are part of the LowpHOX-2 cruise off the northern coast of Chile investigating the distribution of intact polar lipids above, through, and below the oxygen minimum zone at two stations. We report intact polar lipid concentrations in addition to a number of water column chemistry parameters. Used in a manuscript under review at Frontiers in Marine Science.